Procura de energia e políticas públicas para uma utilização responsável - Machado, B. (2018)
Energy is now intrinsically linked to technological and social development, powering all systems. The use of fossil fuels to supply the required energy is causing global environmental and health issues and is impacting on all life forms on the planet. Given the increasing energy use, anthropogenic greenhouse gas emissions are consequentially increasing. A critical and evolutionary way of thinking about the energy and resources demand management and supply is necessary because there is a great concern about the irreversible impacts to the world and the scarcity of the resources as well. At the same time, all the energy and resource use processes should be optimized to maximize the benefits, reduce the costs and promote stakeholders network, toward a circular economy. This could be the way to supply the demand without increasing the scarcity of the resources and to simultaneously achieve environmental benefits. Furthermore, creating an educational grid is essential to change the established paradigms, to promote critical thinking on the wasted resources and thinking holistically about overall consumption. This paradigm shift is changing the market, making it more competitive and reducing inefficiency by promoting the efficient use of resources. The legislation and the public policies that consider sustainability approaches are constantly improving, trying to fix the pathways to avoid climate changes and achieve energy efficiency, but at the same time, the energy and resources demand are still increasing in a no sustainable way, which makes very much urgent the rapid implementation of measures.